K itogam sportivnogo sezona 2000-2001 gg. po plavaniyu - Kulikov, V. I. (Teorija i Praktika fiziceskoj Kul'tury, 2002)
Analysis of the actual situiation in international and Russian swimming. With some words about the preparation and the staff of the Russian team.